Of Relating the Linguistic Description to an Interpretation of a Literary Work (Poetry) - Ali Rabi (Iranian Journal of Applied Language Studies, 2011)
This article attempts to see, through the structural significances of poetic language, the nature of the split between linguistic description and literary interpretation. Rhythm is the most prominent means of relating form to content in poetic language. The first account of this prominence is seen through identifying its position in the two prosodic forms of metrical and non-metrical poetry. Foregrounding has been seen as a significant feature in literary creation. FollowingBradford(1997) the analysis undertakes three stages of analysis as ‘discovery procedures’, ‘naturalization’, and ‘judgment’ (renamed in our work as ‘remarks’). The first level examines the degree of the tension between the two patterns. In the second level, i.e. naturalization, the analysis goes on turning the peculiar language of the poem into that of the ordinary, which means making sense of a text. This translation of the poetic language has been shown to be considerably rooted in elements of form in the classical verse, and of content in modern free verse. The intervening type has thus been judged to exist somewhere between the two. The third level, namely ‘remarks’ evaluates the degree of the poet’s success in managing the tension between the two patterns.